Deformation performance of aramid honeycomb core layer on partial layup structure outside plane - LU Zhengbin; SUN Wei; WEI Ning; LIU Lu; LI Qiong; LYU Xiulei (Journal of Aeronautical Materials)
In the co-curing process of aramid honeycomb sandwich structures with traditional hexagonal core lattice structures，the deformation compatibility of honeycomb with locally varying structures outside the plane is an important factor affecting the internal forming quality of sandwich structures. This article analyzes the out-of-plane local deformation performance of honeycombs using numerical methods by establishing a finite element quantitative analysis model，combining typical structural experimental verification methods，using full-body modeling and elastic mechanics plate bending theory. It explores the influence of key factors such as honeycomb thickness and external pressure on honeycomb deformation，and verifies the local surface fitting method of super-honeycomb deformation limits. The results show that the quantitative analysis model of aramid honeycomb deformation capability，with deflection deformation fitting as the core，has good applicability for predicting the matching state of honeycomb-layered structures. For cases where the slope of the honeycomb deflection fitting curve is less than the transition slope of the layer，honeycomb yield milling has a positive impact on the bonding quality of the transition region of the layer，but different forms of yield milling do not produce significant differences in bonding quality. The relevant results have certain reference value for structural design and process design of honeycomb sandwich structures.